Effects of Compost and Buckling on the Rejection Capacity of Plantain (Musa sapientum L.) under the Eco-climatic Conditions of Gbado-Lite, Democratic Republic of the Congo - Molongo Mokondande Médard; Koto-Te-Nyiwa Ngbolua; Muhammad Ridwan; Taffouo Victor Désiré; Songbo Kwedugbu Médard; Litucha Bakokola Joseph; Okungo Lotokola Albert; Monde-Te-Kazangba Godefroid (Britain International of Exact Sciences (BIoEx) Journal, 2022)
The aim of this study was to evaluate the effect of compost and buckling on the plantain (Musa sp. cv. AAB, var Ngbangele) offshoot power under the conditions of Gbado-Lite in the Democratic Republic of the Congo. The experimental device chosen was that of complete randomized blocks comprising 3 repetitions and 4 plots 3 m long. The plots were arranged so that the flamed cultivars were adjacent depending on the substrates including T0: control substrate or unamended plot; T1: substrate from sawdust; T2: substrate from rice husk; T3: substrate from slush. Each plot contained 10 sample suckers of plantains. The greenhouse was installed after applying the buckling technique. It was observed that a bulb produced an average of 4 weaned suckers in the control bulbs; 8 suckers weaned on bulbs installed on substrates originating from slush; 9 suckers weaned on bulbs planted on substrates made from sawdust and rice husk. The releases installed on the control plot experienced a post-buckling recovery rate of 66.7%; those planted on sawdust and rice husk gave 83.3% and the subjects planted on the substrate from slush experienced a recovery rate of 80%; these results showed that the flame suckers adapted to the greenhouse conditions. In view of these results, it should be noted that this technique remains a major asset for the production of healthy suckers and in large quantities.